Biochemical Status and Cytopathological Profile of Patients Presenting with Multinodular Goiter (Journal of Medicine, 2011)
Background: Objective of the study was to evaluate the biochemical status and cytopathological profile in multinodular goiter. Materials and Methods: 50 patients with multinodular goiter were selected consecutively. Multinodularity was confirmed by ultrasonography and scintiscan of the thyroid gland. Hormonal assays of serum T3, T4 and TSH was done for biochemical status evaluation. Fine needle aspiration cytology (FNAC) was done to evaluate the cytopathological profile of the MNG patients. Results: The patients had a female preponderance with a male to ratio of 5.25:1. Biochemical status evaluation revealed that sixty percent presented with euthyroid features followed by those of hyperthyroidism (16%). The distribution of hypothyroid, subclinical hypo- and hyper- thyroid patients were equal (8% each). Among the clinical and subclinical hyperthyroids there was Jod Basedow. The cytological profile of multinodular goiter showed that two were malignant (found by open biopsy after surgery) and four had suspicious cytology. Conclusion: Though relatively benign, risk of malignancy in multinodular goiter should not be undermined and FNAC should be included in the initial diagnostic procedures during work up of a multinodular goiter. Keyword: Multinodular goiter; Hyperthyroidism; Hypothyroidism; Malignancy; FNAC; Scintigram DOI: 10.3329/jom.v12i1.6928J Medicine 2011; 12 : 26-29